Les Fils de Bas-de-Cuir. Sauvagisme, franc trappeur et « lutte des traces » dans le roman d’aventures français (1850-1880) - Luca Di Gregorio (Transatlantica, 2019)
This paper analyzes the representation of North-American fictional worlds in the French western novel. With writers such as Gustave Aimard (1818-1883), the subgenre was one of the most common adventure serials between 1850 and 1880. The analysis deals with the heroism embodied by the recurring figure of the coureur des bois, a French variety of mountain man who is the main protagonist of these novels. I question the relationship between that character and the fictional West. Through a historical and comparative approach, the coureurs des bois’ adventure will be compared with the classical language of the Western (deciphering vs. settlement, walking vs. mounting, tracking vs. invasion and conquest) so as to insist on the alternative value brought by the adventurous “sauvagisme” (mainly European) in contrast with pioneers/settlers stories which were inspired, during the same period, by the rhetorics of the manifest destiny and the frontier.